Moral authority and status in International Relations: Good states and the social dimension of status seeking. Issue 3 (5th December 2017) - Wohlforth, William C.; de Carvalho, Benjamin; Leira, Halvard; Neumann, Iver B.
Abstract: We develop scholarship on status in international politics by focusing on the social dimension of small and middle power status politics. This vantage opens a new window on the widely-discussed strategies social actors may use to maintain and enhance their status, showing how social creativity, mobility, and competition can all be system-supporting under some conditions. We extract lessons for other thorny issues in status research, notably questions concerning when, if ever, status is a good in itself; whether it must be a positional good; and how states measure it.